Pengaruh Surface Treatment Dengan Sandblasting-Bonding Agent Terhadap Kekuatan Ikatan Geser Antara Gigi Artifisial Akrilik Dengan Basis Gigi Tiruan Nilon Termoplastik - Dzaki, Rinauval (Cerdika: Jurnal Ilmiah Indonesia, 2025)
Tooth loss can affect chewing function, aesthetics, and speaking comfort, ultimately impacting a person's quality of life. One common solution for replacing missing teeth is dentures, which consist of artificial teeth and a denture base. Nylon thermoplastic denture bases have many advantages, such as flexibility and aesthetics, but they have weaknesses in terms of the bond between the artificial teeth and the base. This study aims to investigate the effect of surface treatment with sandblasting and bonding agent on the shear bond strength between acrylic artificial teeth and nylon thermoplastic denture bases. This study uses an experimental laboratory design with control and treatment groups and conducts shear bond strength testing using standard methods. The results indicate that the use of surface treatment with sandblasting and bonding agent significantly improves the shear bond strength between acrylic artificial teeth and nylon thermoplastic denture bases, with the best effect found in the combination of sandblasting and Tetric N Bond Universal bonding agent. These findings contribute to the development of prosthodontic technology to improve the quality and durability of dentures.